Moralitas, Peran Perangkat Desa, Dan Kepatuhan Masyarakat Dalam Membayar Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan: Sanksi Sebagai Variabel Moderating - Amir Hidayatulloh; Agung Dwi Nugroho; Kahfi Fikrianoor (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
This research aims to determine the factors that influence the community in paying property taxes in rural and urban areas, and to find out whether the risk variabel moderates the effect between morality and the role of village official on commuity compliance in paying property taxes in rural and urban areas. The population in this research  is individual taxpayers who in bantul regency. The sample in this research is individual taxpayers who own land and buildings. The research data wase collection by distributing questionnaires to respondents who were met by researchers. Respondents in this research were 127 respondents. This research data analysis techniques uses Partial Least Square, with the help of WarpPLS. This research found that coomunity compliance in paying property taxes in rural and urban areas influenced by the role of village official and sanction. However, morality has no effect on community compliance to property taxes in rural and urban areas. This reserach also found that sanction moderate the effect of morality on the community’s compliance to pay land and urban rural building taxes. However, sanction cannot moderate the effect between role of village officials on community’s mandatory the effect between the role of village official on community’s compliance to pay land and urban rural building taxes.